GUI test case minimization using sequence mining - Raheela Ambreen; Tamim Ahmed Khan (PLoS ONE, 2026)
Graphical User Interface (GUI) testing is a crucial aspect of software quality assurance, ensuring that the user-facing components correctly reflect the underlying business logic. Regression testing validates that software continues to function as expected after modifications or integration with other systems. However, executing large test suites repeatedly is time-consuming and resource-intensive. To address this, test case minimization techniques aim to reduce the number of test cases without compromising coverage. In this work, we propose a sequence recording technique for GUI event tracking and test case minimization. The recorded event sequences are clustered using the K-Means algorithm, grouping highly similar events together. A search-based sequence selection is then applied to generate a representative subset of test cases. Our approach was implemented and evaluated using a User Interface (UI) map generated in Visual Studio, where all components were validated and compared with our event map. Experimental results show that our proposed method reduces the total number of test cases by approximately 45%, decreases execution time by 38%, and maintains over 95% coverage compared to the original test suite. These results demonstrate that the proposed approach effectively balances testing efficiency and coverage, providing a practical improvement for GUI regression testing.